Liquid-microjet photoelectron spectroscopy of the green fluorescent protein chromophore - Omri Tau; Alice Henley; Anton N. Boichenko; Nadezhda N. Kleshchina; River Riley; Bingxing Wang; Danielle Winning; Ross Lewin; Ivan P. Parkin; John M. Ward; Helen C. Hailes; Anastasia V. Bochenkova; et al. (Nature Communications, 2022)
The electronic structures of photoactive proteins underlie many natural photoinduced processes. The authors, using UV liquid-microjet photoelectron spectroscopy and quantum chemistry calculations, determine electron detachment energies of the green fluorescent protein chromophore in aqueous solution, approaching conditions of the protein environment.